PSET Learning through Storyline Curriculum Development - Feille, Kelly (Innovations in Science Teacher Education, 2025)
Current approaches to science education emphasize authentic science learning experiences for students and center the learner as the driver of the classroom experience. One support to help pre- and in-service science teachers meet the goals of a student-centered classroom exists in the form of curricular materials. The storyline unit has the potential to be particularly beneficial as a tool for preservice science teacher education as it serves as a model structure for a student-centered science curriculum that aims to leverage student ideas and connected science learning experiences to facilitate authentic science learning. The innovative practice described in this article utilizes the storyline unit as a curricular tool to support preservice science teacher development through curricular design, evaluation, adaptation, and finally implementation. In grade-level teams of three to four, preservice elementary teachers (PSETs) select a Big Idea from Grades 3-6 to develop a storyline unit using provided tools and scaffolds (templates). The course concludes with grade-level teams launching their storyline through a peer-teaching session that includes the introduction of phenomena and elicitation of initial student ideas. Because of the heavy reliance on curricular materials for science teaching at the elementary level, supporting and investigating curricular role identity development of preservice elementary teachers is important. Engaging PSETs in the co-design of storyline units with an emphasis on evaluation of materials supports the development of a curricular role identity that can support ongoing learning through curriculum materials and the appropriate adaptation and enactment of high-quality instructional materials for their future students.